Structural Integrity Analysis of Containers Lost at Sea Using Finite Element Method - Oterkus, Selda; Wang, Bingquan; Oterkus, Erkan; Galadima, Yakubu Kasimu; Cocard, Margot; Stefanos, Stefanos; Buckley, Jami; McCullough, Callum; Boruah, Dhruv; Gilchrist, Bob (Sustainable Marine Structures, 2022)
Unlike traditional transportation, container transportation is a relatively new logistics transportation mode. Shipping containers lost at sea have raised safety concerns. In this study, finite element analysis of containers subjected to hydrostatic pressure, using commercial software ANSYS APDL was performed. A computer model that can reasonably predict the state of an ISO cargo shipping container was developed. The von Mises stress distribution of the container was determined and the yield strength was adopted as the failure criterion. Numerical investigations showed that the conventional ship container cannot withstand hydrostatic pressure in deep water conditions. A strengthened container option was considered for the container to retain its structural integrity in water conditions. ER